Internalisasi Nilai Islami pada Anak Usia Dini di Tengah Paparan Konten Digital - Hasan Yusuf; Uqbah Muhammad Zilal; Rheina Salsabila; Sya’bani Nurbayan; Salsa Sintiana (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This research aims to examine the process of instilling Islamic values in early childhood amid increasing exposure to digital content and to analyze the contribution of parents and teachers in shaping children’s character. This study used a qualitative approach with a case study design in Islamic-based early childhood education institutions. Data were collected through participatory observation. The findings show that the internalization of Islamic values, including monotheism, morals, discipline, responsibility, and manners, is more effective through habituation, exemplary behavior, positive reinforcement, and the integration of values into directed and controlled digital play and learning activities. Parents serve as the primary companions in building children’s digital literacy in the family environment, while teachers act as learning facilitators and role models in strengthening character at school. Continuous synergy between families and educational institutions strengthens the formation of children’s religious character from an early age. The implication of this research is the need for Islamic value-based digital parenting programs, a value-integrated early childhood curriculum, and teacher capacity building in digital literacy and character education so that digital media can be used as an educational space for holistic child development in the digital era